Implementasi Metode Bernyanyi dalam Mengembangkan Sosial Emosional Anak Usia Dini - Rianti; Sri Hayani; Isty Nurul Hidayati; Rati Kurniati; Solihatun Mufidah (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2022)
The purpose of this study was to describe the implementation of the singing method to improve aspects of children's social-emotional development in TK PGRI Dewi Sartika. The method used in this study is a descriptive qualitative method and is a field research, with TK PGRI Dewi Sartika teacher as the research subject. The collecting data uses observation, documentation and interviews. The data analysis technique uses reduction, display, and verification. The results of this research can show that the singing method is the main method that is always used in every learning activity for children at school. In addition, the singing method is also used to develop the social emotional aspects of children. Through singing, children are very enthusiastic and happy to follow it. This method is used in initial activities,core activities and closing activities. Socio-emotional aspects of children can develop well using the singing method. In addition, children look more enthusiastic and enthusiastic in learning activities carried out using the singing method. Therefore, this method is very appropriate to use to developthe social emotional aspects of children.